2009
DOI: 10.1080/14017430802653676
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of hs-CRP and IL-6 in patients undergoing radiofrequency catheter ablation for atrial fibrillation

Abstract: In patients with a history of paroxysmal or persistent AF treated with RF catheter ablation, elevated levels of IL-6 and hs-CRP before ablation are independent predictors of recurrence of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 25 publications
1
33
1
1
Order By: Relevance
“…In a multivariate logistic regression analysis, the baseline value of plasma YKL-40 was not an independent predictor of recurrent AF after catheter ablation (P = 0.28). The procedure (P = 0.03) and the left atrium diameter (P = 0.02) were still independent predictors of recurrent AF as previously reported [10,24] (Table 3).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…In a multivariate logistic regression analysis, the baseline value of plasma YKL-40 was not an independent predictor of recurrent AF after catheter ablation (P = 0.28). The procedure (P = 0.03) and the left atrium diameter (P = 0.02) were still independent predictors of recurrent AF as previously reported [10,24] (Table 3).…”
Section: Resultssupporting
confidence: 70%
“…In the present population we have previously shown [10] that plasma levels of IL-6 before catheter ablation were an independent predictor of recurrence of AF. In the present study we found that baseline plasma YKL-40 correlated significantly with baseline plasma IL-6, but not with baseline hs-CRP.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Other investigators associated serum IL-6 levels with AF after CABG, 51 after cardioversion, 52 and after radiofrequency catheter ablation. 53 Aviles and associates 22 performed a cross-sectional study of 5,806 subjects and reported that baseline levels of CRP were higher in patients affected by AF even after adjustment for multiple variables potentially associated with AF, and that CRP level is a strong predictor of future AF. Among 5,491 patients included in the longitudinal study, 897 (16%) developed AF during the follow-up period (median duration, 7.8 yr).…”
Section: Correlation Between Atrial Fibrillation and Inflammationmentioning
confidence: 99%